Guiding marine protected area network design with comparative phylogeography and population genomics: An exemplary case from the Southern Ocean. (19th July 2022) - Leiva, Carlos; Riesgo, Ana; Combosch, David; Arias, María Belén; Giribet, Gonzalo; Downey, Rachel; Kenny, Nathan James; Taboada, Sergi
Abstract: Aim: Networks of connected marine protected areas (MPAn) are recognized as the key area‐based management tool to preserve biodiversity, moderate exploitation of marine resources and increase ecological resilience to climate change. Although population genetic studies could greatly benefit connectivity assessments between MPAs, genetic data are rarely used in MPAn planning. Here, we aim to illustrate the use of a multispecies and multilocus approach to provide recommendations for MPAn design, highlighting the importance of the species selected and the analyses performed. Our study is focused on the Southern Ocean, an area of keen multinational interest given its scientific significance, economic importance and its unique, shared legal status. Location: South Georgia and South Sandwich Islands MPA (SGSSI MPA), the South Orkney Islands and the Western Antarctic Peninsula (WAP)—where an MPA was proposed in 2018 (Domain 1 MPA) but has not been approved by the Commission for the Conservation of the Antarctic Marine Living Resources (CCAMLR). Methods: Our datasets include 819 individuals from five different species with contrasting life‐history strategies: two nemerteans ( Antarctonemertes valida and A. riesgoae ), two annelids ( Pterocirrus giribeti and Neanthes kerguelensis ) and one sponge ( Mycale [Oxymycale] acerata ). To identify genetic connectivity patterns in our study area, spanning roughly 2500 km, we used the COI mitochondrial marker and genome‐wide ddRADseq‐derived SNPs. Results: A consistent lack of connectivity between SGSSI MPA and the WAP was found for all studied species. Additionally, our data indicated a stepping‐stone role for the South Orkney Islands between these two genetically differentiated regions. Main conclusions: Our results reveal how the application of comparative phylogeography and population genomics can guide policymakers in their decision‐making process during MPAn design. We detected priority areas for conservation in Antarctica, including the South Orkney Islands and the WAP, providing strong evidence for the implementation of the Domain 1 MPA.